If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(4y + 2) + -1(3y + -4) = -6 Reorder the terms: -1(2 + 4y) + -1(3y + -4) = -6 (2 * -1 + 4y * -1) + -1(3y + -4) = -6 (-2 + -4y) + -1(3y + -4) = -6 Reorder the terms: -2 + -4y + -1(-4 + 3y) = -6 -2 + -4y + (-4 * -1 + 3y * -1) = -6 -2 + -4y + (4 + -3y) = -6 Reorder the terms: -2 + 4 + -4y + -3y = -6 Combine like terms: -2 + 4 = 2 2 + -4y + -3y = -6 Combine like terms: -4y + -3y = -7y 2 + -7y = -6 Solving 2 + -7y = -6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -7y = -6 + -2 Combine like terms: 2 + -2 = 0 0 + -7y = -6 + -2 -7y = -6 + -2 Combine like terms: -6 + -2 = -8 -7y = -8 Divide each side by '-7'. y = 1.142857143 Simplifying y = 1.142857143
| Y^2-9Y+20= | | p-44=-42 | | 4.4q-1.3-3.8q=0.4q-1.3 | | 9+19s-2=7s+55-4s | | 7n+6n=52 | | X^2+7Y+12= | | 1.4q-1.3-2.8q=-2.4q-2.9 | | -3y+1=-4y+5 | | Y^2-3Y-4= | | p-38=-27 | | 15y^2+31y+10=0 | | 7-y=9 | | 8x^2+24=0 | | 6x^2+78x-144=0 | | Z^2+8Z+15= | | 8(t-6)+4t=6(2t+2)-11 | | 6x^2+78x-24=0 | | 2x^2+8x=1 | | Y^2+10Y-24= | | -8.6x=25.8 | | Y^2-8Y-33= | | .42x=10 | | -3(2b+4)+(7b-3)=0 | | n*0.04x-78.40= | | 4a+2a=24 | | 5+9lnx=41 | | x-7.4=-6.7 | | X^2+2-20= | | 0.0003q^2-0.14q+36=0 | | s+33=20 | | (3s^2+4s-3)(s^2+2s+4)= | | 5+9ln(x)=41 |